Transporting newborn infants with suspected duct dependent congenital heart disease on low-dose prostaglandin E1 without routine mechanical ventilation. Issue 2 (11th August 2006) - Browning Carmo, Kathryn A; Barr, Peter; West, Maureen; Hopper, Neil W; White, Jennifer P; Badawi, Nadia
Abstract : Aim: To evaluate the safety of transporting newborn infants with suspected duct dependent congenital heart disease (CHD) treated with prostaglandin E1 (PGE1) without routine mechanical ventilation. Methods: A retrospective population-based audit of newborn infants with suspected CHD transported on PGE1 by the New South Wales newborn and paediatric Transport Service from 1995 through 2005. Results: Mechanical ventilation was not used prior to treatment with PGE1 in 94 (31%) of the 300 infants. The indications for mechanical ventilation in the remaining 206 infants (69%) included elective mechanical ventilation because of the intention to use PGE1 (n = 125) and severe hypoxaemia, acidosis or cardiorespiratory failure prior to commencing PGE1 (n = 81). 16 (17%) of the 94 infants who were not ventilated initially required mechanical ventilation before transport because of apnoea, which developed within one hour of commencing PGE1. 2 (2.6%) of the 78 infants transported without mechanical ventilation developed apnoea in transit and both were receiving ⩾15 ng/kg/min of PGE1. Apnoea was more likely to occur in non-ventilated infants when the PGE1 infusion rate was ⩾15 ng/kg/min compared with <15 ng/kg/min (14/33 vs 4/61, χ 2 = 15.55, p<.001). Conclusions: Newborn infants with suspected duct dependent CHD treated with low dose PGE1 (<15 ng/kg/min) may not require mechanical ventilation for safe transport.